Enhanced cell functions on graphene oxide incorporated 3D printed polycaprolactone scaffolds - Unagolla, Janitha M. (Mater Sci Eng C Mater Biol Appl, 2019)
For tissue engineering applications, a porous scaffold with an interconnected network is essential to facilitate the cell attachment and proliferation in a three dimensional (3D) structure. This study aimed to fabricate the scaffolds by an extrusion-based 3D printer using a blend of polycaprolactone (PCL), and graphene oxide (GO) as a favorable platform for bone tissue engineering. The mechanical properties, morphology, biocompatibility, and biological activities such as cell proliferation and differentiation were studied concerning the two different pore sizes; 400 μm, and 800 μm, and also with two different GO content; 0.1% (w/w) and 0.5% (w/w). The compressive strength of the scaffolds was not significantly changed due to the small amount of GO, but, as expected scaffolds with 400 μm pores showed a higher compressive modulus in comparison to the scaffolds with 800 μm pores. The data indicated that the cell attachment and proliferation were increased by adding a small amount of GO. According to the results, pore size did not play a significant role in cell proliferation and differentiation. Alkaline Phosphate (ALP) activity assay further confirmed that the GO increase the ALP activity and further Elemental analysis of Calcium and Phosphorous showed that the GO increased the mineralization compared to PCL only scaffolds. Western blot analysis showed the porous structure facilitate the secretion of bone morphogenic protein-2 (BMP-2) and osteopontin at both day 7 and 14 which galvanizes the osteogenic capability of PCL and PCL + GO scaffolds.